TEMPORARY COMMERCIAL SPACES IN SOFIA: TYPES AND POTENTIAL - Lombardi, Carmella (Innovation in Woodworking Industry and Engineering design, 2025)
This article examines the phenomenon of temporary commercial spaces as a dynamic and increasingly popular format in the modern urban environment. The introduction presents the essence of these spaces, their main characteristics and functions, drawing on existing research and perspectives of leading authors in the field. Based on the literature review, the article offers an author’s classification of the types of temporary commercial spaces, consistent with their functions, duration and form of implementation. The empirical part includes an analysis of two different types of bazaars in Sofia, studied through personal observations and interviews with organizers and participants. In conclusion, possible improvements for the future development of temporary commercial spaces in Sofia are formulated.